Combinatorial therapy using RNAi and curcumin nano-architectures regresses tumors in breast and colon cancer models - Kumar, Aviral; Singam, Amarnath; Swaminathan, Guruprasadh; Killi, Naresh; Tangudu, Naveen Kumar; Jose, Jedy; Gundloori, Rathna V. N.; Kumar, Lekha Dinesh (Nanoscale, 2022)
Cancer is a debilitating disease and one of the leading causes of death in the world. In spite of the current clinical management being dependent on applying robust pathological variables and well-defined therapeutic strategies, there is an imminent need for novel and targeted therapies with least side effects. RNA interference (RNAi) has gained attention due to its precise potential for targeting multiple genes involved in cancer progression. Nanoparticles with their enhanced permeability and retention (EPR) effect have been found to overcome the limitations of RNAi-based therapies. With their high transportation capacity, nanocarriers can target RNAi molecules to tumor tissues and protect them from enzymatic degradation. Accumulating evidence has shown that tyrosine kinase Ephb4 is overexpressed in various cancers. Therefore, we report here the development and pre-clinical validation of curcumin-chitosan-loaded: eudragit-coated nanocomposites conjugated with Ephb4 shRNA as a feasible bio-drug to suppress breast and colon cancers. The proposed bio-drug is non-toxic and bio-compatible with a higher uptake efficiency and through our experimental results we have demonstrated the effective site-specific delivery of this biodrug and the successfull silencing of their respective target genes in vivo in autochthonous knockout models of breast and colon cancer. While mammary tumors showed a considerable decrease in size, oral administration of the biodrug conjugate to Apc knockout colon models prolonged the animal survival period by six months. Hence, this study has provided empirical proof that the combinatorial approach involving RNA interference and nanotechnology is a promising alliance for next-generation cancer therapeutics.